Analisis Pemasaran dalam Rangka Peningkatan Efisiensi Pasar Ikan Tangkap - Fuji Aryani; Nia Rosiana (Jurnal Ilmiah Membangun Desa dan Pertanian, 2024)
Marine fish production in PPN Palabuhanratu fluctuates every year. This condition impacts fish prices at the producer and consumer levels. The low cost of fish is one of the problems with PPN Palabuhanratu. In addition, perishable products affect the importance of an efficient marketing process so that fish can reach consumers fresh. The research aims to analyze the marketing to increase fish catches, especially efficiency in madidihang tuna in PPN Palabuhanratu. This research was conducted from November 2022 to June 2023, interviewing ten respondents from 10 sample ships. The study used three methods (purposive sampling, accidental sampling, and snowball sampling). Primary and secondary data are used in this research to calculate marketing margin, fishermen's share, and profit-cost ratio. The result is four marketing channels, the most efficient being the marketing channel from traders, fishermen, and consumers. This is because this channel has the smallest margin value, the highest fishermen's share value, and the profitable value of cost benefits.